2022
DOI: 10.15447/sfews.2022v20iss1art2
|View full text |Cite
|
Sign up to set email alerts
|

Counting the Parts to Understand the Whole: Rethinking Monitoring of Steelhead in California’s Central Valley

Abstract: Steelhead (Oncorhynchus mykiss expressing an anadromous life history) in the Sacramento and San Joaquin rivers and their tributaries in California’s Central Valley (CCV) belong to a Distinct Population Segment (DPS) that is listed as threatened under the US Endangered Species Act. Although contemporary management and recovery plans include numerous planned and ongoing efforts seeking to aid in DPS recovery—such as gravel augmentation, manipulation of spring flows, and restoration of rearing and spawning habita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 55 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…Within all CCV steelhead hatchery programs, the RR genotype associated with expression of faster development and residency (Pearse et al, 2019;Rundio et al, 2021) was found at low frequencies, consistent with previous observations that southern O. mykiss populations below barriers to anadromy possess high frequencies of the A haplotype at Omy05, particularly in the CCV (Abadía-Cardoso et al, 2019;Eschenroeder et al, 2022;Leitwein et al, 2017;Pearse et al, 2019;Pearse & Campbell, 2018). In addition, Omy05 genotype frequencies significantly deviated from HWE in two programs (FRH and NH).…”
Section: Distinct Genetic Lineagessupporting
confidence: 88%
See 2 more Smart Citations
“…Within all CCV steelhead hatchery programs, the RR genotype associated with expression of faster development and residency (Pearse et al, 2019;Rundio et al, 2021) was found at low frequencies, consistent with previous observations that southern O. mykiss populations below barriers to anadromy possess high frequencies of the A haplotype at Omy05, particularly in the CCV (Abadía-Cardoso et al, 2019;Eschenroeder et al, 2022;Leitwein et al, 2017;Pearse et al, 2019;Pearse & Campbell, 2018). In addition, Omy05 genotype frequencies significantly deviated from HWE in two programs (FRH and NH).…”
Section: Distinct Genetic Lineagessupporting
confidence: 88%
“…The CCV contains the Sacramento‐San Joaquin River system, a highly impacted region that occupies the central part of California (Figure 1 ). This low‐elevation area has warmer seasonal temperatures compared with northern O. mykiss habitats (Eschenroeder et al., 2022 ; McEwan, 2001 ). Landscape and hydrograph alterations from dams built over more than a century have reduced access to over 80% of previous salmonid spawning grounds and homogenized temperature and flow profiles, contributing to decreased numbers of anadromous steelhead (Eschenroeder et al., 2022 ; He & Marcinkevage, 2017 ; Lindley et al., 2006 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also documented that artificially supplementing riverine habitat with food may impart a growth benefit (Boughton, Gibson, Yedor, & Kelley, 2007). As differential growth across habitats is relatively common in fish in a broad range of environments, our methods are broadly applicable and could be applied to numerous systems to investigate the differential growth between habitats, including river/ocean life histories for steelhead/ rainbow trout (Eschenroeder et al, 2022), time remaining on spawning grounds post spawning for sturgeon (Moser et al, 2016), warm water habitat for cold water river fish (Armstrong et al, 2021), mangrove habitats (Laegdsgaard & Johnson, 2001), lake bottom sediment type (Bowen, 1984), and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Pairing the counting device with photographs of passage events allows us to validate 100% of passages, thus minimizing any potential for estimation bias due to non-fish objects or other fish species triggering the devices (Putt et al 2022). Steelhead do occur in the Stanislaus and Tuolumne rivers, although infrequently (Eschenroeder et al 2022), and photographs from the device are sufficient to distinguish them from Chinook Salmon. Lastly, the narrow width of the device swim channel (30 cm) and the sensitivity of the infrared beams make it possible to detect and count individuals passing downstream through the device, which are then subtracted from upstream counts for total passages.…”
Section: Discussionmentioning
confidence: 99%